The use of antimicrobial agents in COVID-19 and infections: what we know (Research, Society and Development, 2020)
Today, COVID-19 is causing a worrisome public health emergency and mortality is rising rapidly around the world. At the current time of the pandemic, although there has been much persistence in diagnosing several patients with symptoms or close contacts, there are no definitive guidelines for the initial therapeutic approach for them and, therefore, many patients are dying from a hyperinflammatory immune reaction labeled a "cytokine storm". The use of antimicrobials in the treatment and prevention of COVID-19, caused by the new SARS-CoV-2 coronavirus, is on the rise. Antibiotics used to treat staphylococcal infection, previously showed efficacy to inhibit the first stage of MERScoronarivus viral cycle in human cells. This activity is conserved in SARS-Cov-2, placing its use as a potential treatment for patients with this virus. A literature review using the PubMed, LILACS and Scielo databases was performed, with the terms "Covid", "antibiotic, "therapy" and "microbial resistance" and equivalents in English. In this review, we discussed some important points dedicated to the management of patients with COVID-19 using antibiotics.